2020
DOI: 10.1177/0309364619868364
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of pressure feedback to socket design and fabrication

Abstract: Background: The clinical utility of measuring pressure at the prosthetic socket-residual limb interface is currently unknown. Objectives: This study aimed to identify whether measuring interface pressure during prosthetic design and fabrication results in closer agreement in pressure measurements between sockets made by different clinicians, and a reduction in pressure over areas of concern. It also investigated whether clinicians value knowing the interface pressure during the fabrication process. Study desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…Accepting practical limitations, simplifications were made to match the most common approaches taken by the FEA community, such as the use of a single, nominally homogeneous soft tissue analogue structure [16]. The model permits limited knee flexion, where a fixed knee joint has been used in some FE approaches, and residual limb models or simulators [41,42], which were designed to allow assessment of the residuum-socket interface. Further, the material is more closely matched to transtibial residuum tissue properties than many modelling studies that continue to use a stiff, 200 kPa linear elastic model [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accepting practical limitations, simplifications were made to match the most common approaches taken by the FEA community, such as the use of a single, nominally homogeneous soft tissue analogue structure [16]. The model permits limited knee flexion, where a fixed knee joint has been used in some FE approaches, and residual limb models or simulators [41,42], which were designed to allow assessment of the residuum-socket interface. Further, the material is more closely matched to transtibial residuum tissue properties than many modelling studies that continue to use a stiff, 200 kPa linear elastic model [16].…”
Section: Discussionmentioning
confidence: 99%
“…This development provides an additional dimension to residual limb interface simulators [ 41 , 42 ], by providing a volumetric strain assessment. Non-invasive Digital Image Correlation (DIC) has also been demonstrated to offer some insights into residuum biomechanics, capturing in vivo the shape and free-deformation of the transtibial residual limb [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the pain region felt by the patient is among the PS regions. 14 Therefore, we believe that the PS regions should bear as little load as possible, and the difference in bearing load between other regions should be reduced to avoid excessive load on a certain region. In this way, on the one hand, the risk of muscle atrophy caused by hypoxia of the residual limb because of excessive pressure on the residual limb can be reduced.…”
Section: Methodsmentioning
confidence: 99%
“…12,13 Armitage et al found that it was reasonable to adjust the socket with reference to the pressure value in clinical decision making. 14…”
Section: Introductionmentioning
confidence: 99%
“…Determining the topological differences that cause volume change are critical for clinical use in socket reproduction, as certain residuum regions are more sensitive to increased pressures created by the socket wall topography [29]. It should be noted that many of the studies discussed used residuum casts or substitutes for evaluation and that additional errors will be present when using the techniques on patient's residuums.…”
Section: Introductionmentioning
confidence: 99%